Performance Evaluation of Islamic Healthcare Institutions: A Systematic Review of Sharia Compliance, Governance, and Operational Excellence - Tuti Setiatin; Apollo Daito; Zulkifli Zulkifli (Universitas KH. Abdul Chalim Mojokerto, 2026)
The proliferation of sharia-based healthcare institutions has intensified demand for performance evaluation frameworks that reconcile Islamic principles with contemporary management standards. This study undertakes a systematic literature review to identify and synthesise the existing body of knowledge on performance evaluation of Islamic hospitals, examining three interrelated dimensions: sharia compliance, governance, and operational excellence. Following the PRISMA 2020 protocol, forty-five articles drawn from internationally reputed databases covering the period 2016-2025 were analysed. Findings reveal that performance evaluation in Islamic healthcare settings calls for a holistic integration of spiritual and business imperatives. Sharia compliance encompassing ethics-based patient care, Sharia Supervisory Board oversight, and periodic sharia auditing is positively associated with Muslim patient satisfaction. Islamic corporate governance foregrounds dual accountability to stakeholders and to God, operationalised through mechanisms such as Islamic Social Reporting. Operational excellence, measured through efficiency, effectiveness, and service quality indicators, gains distinctiveness when embedded in Islamic values. The Maqasid al-Shariah framework serves as an overarching evaluative lens that ties these three dimensions together. This review contributes a holistic evaluation model and offers practical implications for hospital managers seeking to design sharia-aligned performance measurement systems.